ADAPTING TO DIFFERENT CLASSROOM ENVIRONMENT.THE TEACHER’S ROLE IN DIFFERENT CONTEXTS - Umurkulova Gulnoza Ismoilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
The modern education system requires the teacher not only to be a provider of knowledge, but also to be an innovative thinker and psychologically sensitive person, adaptable to the social environment. Also, the fundamental reforms being implemented in the education system, in their content and essence, indicate the formation of a creative and inquisitive pedagogical personality who thinks in a new way, can find the right path in the rapidly changing information flow based on the requirements of the time, can analyze information and effectively use it in the educational process and in professional learning as one of the urgent tasks. This, in turn, puts forward not only the professional knowledge of teachers, but also their personal qualities, thinking, openness to innovation and the level of readiness for renewal as an important criterion. Each class has its own unique environment, and this environment directly affects the teacher’s approach and methodology. Therefore, the teacher must review and change his role and activities in each context.